Service productisation as a customer-oriented solution for enhancing service characteristics : A case study in B2B technical wholesale sector - Ketola, Otto (My University, 2019)
This thesis examines the theoretical background of service productisation and its application for overcoming the challenges related to the intangible nature of services. The objective of this thesis is to form a better theoretical understanding of service productisation and to examine the importance of customer-orientation as part of this process. The thesis reviews existing service marketing literature on productisation and combine these theories with the customer-oriented approaches of service-dominant logic. Based on this literature review, a theoretical framework for customer-oriented service productisation process is constructed. The theoretical part of this thesis is reinforced with an empirical study focusing on a case company operating in the technical wholesale business. The suggested framework is aimed towards clarifying the process of service productisation and the tasks and methods included in this process. The findings of this thesis suggest that service productisation is a customer-oriented development approach that can be used to addresses the operational and commercial challenges created by the abstract and intangible nature of services. This is done through a productisation process that focuses on the service offering, professional expertise and service processes. Furthermore, the service productisation process includes both internal organisation-related and external customer-related tasks. Thus, the role of the customer is highly essential for the successful productisation of a service.
Keywords: Service productisation; Service-dominant logic; Service quality; Customer value; B2B services; fi=Markkinointi|en=Marketing|; fi=Markkinoinnin johtamisen maisteriohjelma|en=Master's Programme in Marketing Management|